Hand Vein Pattern Recognition using Natural Image Statistics - kumar, T. Anantha; Premalatha, K.; Natarajan, A.M. (Defence Science Journal, 2015)
Biometrics is the science of identifying a person using physiological or behavioural characteristics. Hand vein pattern is a recent and unique biometric feature which is used for high secure authentication of individuals. The dorsal hand contains dorsal metacarpal veins, dorsal venous network, cephalic vein and basilic vein. This paper presents an image descriptor which uses statistical structure of natural images. In this work, stack of natural image patches are used as filters and these transform an image into integer labels describing the small-scale appearance of the image. These labels are converted into histogram and it is used for further image analysis. The feature space contains binarized statistical image features. The proposed work is tested on NCUT dataset with state-of-the-art algorithms. The experimental results demonstrate that the proposed work outperforms of the state-of-the-art algorithms with the recognition rate of 99.80 per cent. Defence Science Journal, Vol. 65, No. 2, March 2015, pp.150-158, DOI:http://dx.doi.org/10.14429/dsj.65.7312